Identifikasi Mental Computation Siswa Disleksia dalam Melakukan Operasi Penjumlahan dan Pengurangan Bilangan Bulat - Sadieda, Lisanul Uswah; Cahyani, Agustin Eka (UIN Sunan Ampel Surabaya, 2017)
To describe mental computation strategies of the dyslexic student in performing the addition and subtraction of 1-digit and 2-digit integer. Mental computation is a process of doing arithmetic calculations without using other tools. This strategy will help dyslexic students find more accurate and flexible solution while solving the arithmetic problem because it can minimize their weaknesses in terms of reading and writing. This research uses the qualitative approach. Data were collected by using a task-based interview for two dyslexic students. The results of this study indicate that dyslexic students use the spin-around strategy to solve the addition for the 1-digit number and the working from the right and from the left strategies to solve the addition for the 2-digit number. Meanwhile, to solve the subtraction problem, dyslexic students use think addition and counting back strategies for the 1-digit number and Working from The Right strategy for the 2-digit number.